2020
DOI: 10.1155/2020/8093293
|View full text |Cite
|
Sign up to set email alerts
|

Medication-Related Osteonecrosis of the Jaw with Spontaneous Hemimaxilla Exfoliation: Report of a Case in Metastatic Renal Cancer Patient under Multidrug Therapy

Abstract: Medication-related osteonecrosis of the jaw (MRONJ) is a well-recognized complication of drug therapies for bone metabolic disorders or cancer related to administration of antiresorptive (bisphosphonates and denosumab) and antiangiogenic drugs. This report describes an advanced and unusual case of stage III peri-implantitis-induced MRONJ involving the right upper jaw which was attempting to self-exfoliate. A 61-year-old male patient, rehabilitated with the placement of two implants when he was still healthy, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Long-term antibiotic administration may promote the development of resistant strains. Case have also been reported in which MRONJ progressed after prolonged conservative treatment and required extended resection [8] . A position paper of the American Association of Oral and Maxillofacial Surgeons (AAOMS) reported in 2022 also included surgery as an option for MRONJ treatment [9] .…”
Section: Discussionmentioning
confidence: 99%
“…Long-term antibiotic administration may promote the development of resistant strains. Case have also been reported in which MRONJ progressed after prolonged conservative treatment and required extended resection [8] . A position paper of the American Association of Oral and Maxillofacial Surgeons (AAOMS) reported in 2022 also included surgery as an option for MRONJ treatment [9] .…”
Section: Discussionmentioning
confidence: 99%
“…MRONJ is a well-recognized complication of drug therapies for bone metabolic disease or cancer. Antiresorptive drugs, such as bisphosphonates and denosumab, are been used in low and high doses, and a recent literature review identified a range of other medications classified as tyrosine kinase inhibitors, monoclonal antibodies, mammalian target of rapamycin inhibitors, radiopharmaceuticals, selective estrogen receptor modulators, and immunosuppressants that have been implicated in MRONJ in addition to the drugs already mentioned [22]. Many studies have investigated the mechanism of MRONJ development and various therapeutic methods have been proposed but still poorly understood [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…Very recently, another case of a 61-years old male patient who developed an advanced and unusual case of stage 3 peri-implantitis-induced MRONJ involving the right upper jaw was described by Bennardo et al [ 47 ]. For a metastatic RCC, starting from May 2017, the patient received interleukin-2 subcutaneously 3 weeks a month, twice a day for 5 days a week, and then, from June 2017, bevacizumab, every 2 weeks, for 6 months.…”
Section: Onj In Thyroid Cancer Patients Treated With Tkimentioning
confidence: 99%